Hydrogen-Rich Water Consumption for Acute and Residual Fatigue After Simulated Football Matches: Protocol for a Randomized, Double-Blinded, Placebo-Controlled, Parallel Trial - Hruby, Michal; Hulka, Karel; Bernatik, David (JMIR research protocols, 2025)
BACKGROUND: Football matches induce acute and residual fatigue, impairing neuromuscular, metabolic, and perceptual performance. Hydrogen-rich water (HRW) is a novel intervention with antifatigue and antioxidative properties. The intermittent high-intensity nature of football, which includes frequent accelerations, decelerations, sprints, changes of direction, and physical contacts, imposes substantial demands on both central and peripheral physiological systems. This results in acute fatigue, observable during or immediately after a match, and residual fatigue, which can persist for 24-72 hours post match, depending on the intensity, match context, and recovery strategies. OBJECTIVE: This study will investigate the effects of pre-exercise HRW administration versus a placebo on neuromuscular performance, biochemical markers, and perceptual measures of fatigue during a 72-hour recovery after a simulated football match. METHODS: Using a randomized, double-blinded, placebo-controlled, parallel design, elite junior football players will undergo neuromuscular performance assessments (repeated sprint ability and countermovement jump test). Metabolic fatigue will be measured by creatine kinase level and muscle soreness, rated using a visual analog scale. These assessments will occur at critical time points: immediately post warm-up; directly following the simulated football match to detect acute fatigue; and 24, 48, and 72 hours after training sessions to detect residual fatigue. RESULTS: Data collection has been scheduled with the clubs to coincide with the beginning of the players' transition period (ie, at the start of August 2025). The expected duration of data collection, including the initial medical examination, is planned to be 1 month. We anticipate publishing the results in late 2025 or during the first half of 2026. CONCLUSIONS: This study will assess the influence of molecular hydrogen on acute fatigue manifestation and recovery quality during a 72-hour period after a simulated football match. The potential positive effects of molecular hydrogen, such as attenuation of oxidative stress, reduction in muscle damage markers, and accelerated neuromuscular recovery, may contribute to faster restoration of functional capacities. If confirmed, these effects could enhance players' readiness to return to high-intensity training and optimize the structure of microcycles in competitive periods. Additionally, understanding the recovery dynamics facilitated by HRW may inform evidence-based recovery strategies and support individualized player monitoring frameworks. The possible positive effect of molecular hydrogen would speed up the players' readiness to train after the match and help protect players against illness and noncontact injuries.
Keywords: Randomized Controlled Trials as Topic; vodík; readiness to play; mladý dospělý; oxidative stress; únava; Adolescent; svalová únava; Soccer; Athletic Performance; lidé; Fatigue; dvojitá slepá metoda; recovery; fotbal; voda; Water; Hydrogen; Double-Blind Method; Male; antifatigue effect; Muscle Fatigue; Young Adult; sportovní výkon; randomizované kontrolované studie jako téma; repeated sprint ability; mužské pohlaví; molecular hydrogen; mladiství; Humans